Phenotypic variability for horticultural and fruit quality attributes in plastic house grown tomato - Adeniji, O T; Tenebe, A V; Ishaka, A; Jandong, E; Adamu, J T; Adekoya, M; Zamzam, M A; Aremu, C A (Journal of Horticultural Sciences, 2020)
In Sudan's agro-ecological zone, tomato production is constrained by a dearth of high fruit yielding and quality (Solanum lycopersicum [L.]) varieties for cultivation in polyhouse. Exotic and indeterminate tomato genotypes with high fruit yield and quality were evaluated to gain information on variation for fruit yield, quality, shape, and interdependence between traits in Sudan agroecology. The seed was sown during 2018 and 2019. Fruit yield, quality, and phenomic traits were measured. Development, °Brix, and fruit yield responded to microclimate factors in the polyhouse over years. ‘Bruno’ was the best for fruit size and ‘Tofi’ for fruit number. Vine length at flowering, fruits/cluster, days to 50% flowering, and days to first flowering and fruit brix are heritable. The genotype responses suggest the need for stable and to develop high-yielding and quality tomato varieties for protected cultivation in the Sudan agro-ecological zone. Testing stable genotypes in locations could enhance breeding efficiency with respect to genotypic stability. The yield data gained under tropical conditions identified traits of superior genotypes for multiple environment studies and to encourage tomato growers to consider protected cultivation in the tropics.
Keywords: Character correlation; Fruit quality; Fruit shape; Fruit yield variability; Genotype by environment; Polyhouse; Solanum lycopersicum